2003
DOI: 10.18388/abp.2003_3706
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a constitutively active mutant of heat shock factor 1 under the control of testis-specific hst70 gene promoter in transgenic mice induces degeneration of seminiferous epithelium.

Abstract: Heat shock activates in somatic cells a set of genes encoding heat shock proteins which function as molecular chaperones. The basic mechanism by which these genes are activated is the interaction of the specific transcription factor HSF1 with a regulatory DNA sequence called heat shock element (HSE). In higher eukaryotes HSF1 is present in unstressed cells as inactive monomers which, in response to cellular stress, aggregate into transcriptionally competent homotrimers. In the present paper we showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…It has been previously observed that expression of this constitutively active form of HSF1 in spermatocytes of transgenic mice induces massive apoptosis (Nakai et al . 2000;Widlak et al . 2003a;Vydra et al .…”
Section: Active Hsf1 Down-regulates Hsp702 Expressionmentioning
confidence: 88%
See 4 more Smart Citations
“…It has been previously observed that expression of this constitutively active form of HSF1 in spermatocytes of transgenic mice induces massive apoptosis (Nakai et al . 2000;Widlak et al . 2003a;Vydra et al .…”
Section: Active Hsf1 Down-regulates Hsp702 Expressionmentioning
confidence: 88%
“…However, hypothetical HSF1-dependent factor(s) involved in negative regulation of Hsp70.2/Hst70 and other testis-specific genes remain to be identified. Apparently, elimination of spermatocytes by apoptosis cannot contribute significantly to down-regulation of HSP70.2 detected in 18-day-old pHST-HSF1∆RD transgenic males because massive HSF1dependent apoptosis and degeneration of seminiferous epithelium are observed in older animals (Widlak et al 2003a;Vydra et al 2006).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations